A comparative study of the coordination behavior of cyclo-P5 and cyclo-As5 ligand complexes towards the trinuclear Lewis acid complex (perfluoro-ortho-phenylene)mercury. Issue 1 (22nd October 2014) - Fleischmann, Martin; Jones, James S.; Gabbaï, François P.; Scheer, Manfred
Abstract : Reactions of the cyclo -E5 sandwich complexes [Cp*Fe(η 5 -P5 )] (1 ) and [Cp*Fe(η 5 -As5 )] (2 ) with the planar Lewis acid [( o -C6 F4 Hg)3 ] (3 ) afford compounds that show distinctly different assemblies in the solid state. Abstract : Reactions of the cyclo -E5 sandwich complexes [Cp*Fe(η 5 -P5 )] (1 ) and [Cp*Fe(η 5 -As5 )] (2 ) with the planar Lewis acid trimeric (perfluoro- ortho -phenylene)mercury [( o -C6 F4 Hg)3 ] (3 ) afford compounds that show distinctly different assemblies in the solid state. The phosphorus containing ligand1 forms dimeric coordination units with two molecules of3, with one P atom of each cyclo -P5 ligand positioned in close proximity to the center of a molecule of3 . In contrast to the coordination behavior of1, the arsenic analog2 shows simultaneous interaction of three As atoms with the Hg atoms of3 . A DFT study and subsequent AIM analyses of the products suggest that electrostatic forces are prevalent over donor–acceptor interactions in these adducts, and may play a role in the differences in the observed coordination behavior. Subsequently, a series of [Cp R Fe(η 5 -P5 )] (Cp R = C5 H5− n t Bu n, n = 1–3, 6a–c ) sandwich complexes was prepared and also reacted with [( o -C6 F4 Hg)3 ]. In the solid state the obtained products7a–c with increasing steric demand of the Cp R ligands show no significant change in their assembly compared to the Cp* analog4 . All of the products were characterized by single crystal X-ray structure analysis, mass spectrometry and elemental analysis as well as NMR spectroscopy and IR spectrometry.